Late gestation lysine and energy effects in sows and dose-responses to tryptophan and valine in finishing pigs - Gonçalves, Márcio Antônio Dornelles (Kansas State University, 2015)
The overall goal of this dissertation was to evaluate the effects of different amino acid (AA) levels on performance of pigs under commercial conditions. To reach this objective, a total of 12 experiments were conducted. For the sow research, 1,102 highly prolific sows were used to determine the effects of AA and energy intake during late gestation on piglet birth weight and reproductive performance of sows. Weight gain depended on the energy and AA intake levels while sows fed increased amount of energy had increased stillborn rate; however, there was no statistical differences due to energy intake in stillborn rate of gilts. The modest increase in individual piglet birth weight is due to energy rather than AA intake during late gestation. Pre-weaning mortality was reduced in piglets suckling from sows fed high AA diets during late gestation while subsequent reproductive performance was not affected. With recent advances in statistical computing capability, linear and non-linear mixed models were refined to estimate the AA ratio dose-response relationships. Then, 4 experiments using 2,420 wean-to-finish pigs were conducted to validate the methods for estimating the standardized ileal digestible (SID) AA to lysine (AA:Lys) ratio requirement. Subsequently, 7 experiments using 7,562 pigs were conducted to estimate the SID tryptophan (Trp) to Lys and Valine (Val) to Lys ratio requirements of wean-to-finish pigs. In 11- to 20-kg pigs, optimum SID Trp:Lys ranged from 16.6% for maximum mean G:F to 21.2% for ADG. In 30- to 125-kg pigs, optimum SID Trp:Lys ratio ranged from 16.9% for maximum mean G:F to 23.5% for ADG. However, 18% SID Trp:Lys captured 96 and 100% of the maximum mean ADG and G:F for finishing pigs, respectively. In 25- to 45-kg pigs, optimum SID Val:Lys ratio ranged from 72.3% for maximum mean G:F to 74.4% for ADG with 99% of the maximum mean ADG and G:F at approximately 69% and 65% SID Val:Lys ratio, respectively. In conclusion, optimum SID Trp:Lys and Val:Lys were consistently higher for ADG than G:F. This finding is critical for conducting economic evaluations and reference tables such as NRC (2012) should consider presenting requirement values for different response criteria.
Keywords: Lysine; Tryptophan; Valine; Energy; Sows; Pigs; Animal Sciences (0475); Statistics (0463); Veterinary Medicine (0778)